Rethinking 'flexible' capitalism: exploring the formation of 'flexible' capitalism in Turkey through the case of the shipyards of Tuzla / Istanbul - Ağırnaslı, Suphi Nejat, 1984-2014. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This thesis deals with the formation of capitalist conduct in and around the shipyards of Tuzla (Istanbul). The complex web of relation between governmental policies, shipyard owners, ship owners, subcontractors and workers are conceived of upon the concept of ‘flexibility’. This concept does not assume a qualitative new form of capitalism but is deployed as a methodology, which puts capitalism within the problematic of power and subjectivity. The multiplicity of relationships and contestations in and around the shipyards of Tuzla shall lead to an understanding of capital accumulation, which is understood as an attempt to universalize potentialities. It shall be argued that this very process is operative in that this attempt is steadily disrupted and thus leads to a reorganization of the forms to distribute power, contest it and contain resistances.
Keywords: Flextime -- Social aspects -- Turkey.